Unprecedented Plasmon-Induced Nitroxide-Mediated Polymerization (PI-NMP): a Method for Preparation of Functional Surfaces - Guselnikova O.; Marque S.; Tretyakov E.; Mareš D.; Jeřábek V.; Audran G.; Joly J.-P.; Trusova M.; Svorcik V.; Lyutakov O.; Postnikov P. (Royal Society of Chemistry, 2019)
A plasmon as a stimulus opens up new opportunities for selective and regulated “from-surface” polymerization and functionalization of surfaces. Here, the first example of plasmon-assisted nitroxide-mediated polymerization (NMP) of stimuli-responsive block copolymers poly(N-isopropylacrylamide)-co-4‐vinylboronic acid is reported. The growth of polymer film at room temperature was achieved via plasmon-induced homolysis of alkoxyamines covalently attached to the surface of plasmon-active gold gratings at room temperature. Control of temperature, finite-difference time-domain method simulation of plasmon intensity distribution shift during polymerization, electron paramagnetic resonance experiments, and other assays provide strong support for the plasmon-initiated mechanism of NMP. We demonstrated not only the control of resulting polymer thickness but also the preparation of a SERS chip for detection of glycoproteins as a powerful example of plasmon-assisted NMP potential.
Keywords: plasmon; NMP; SERS; polymerization; grating